Citizens Relationship Management (CRM) in Jakarta: Does its work or not? - Salsabila, Lubna; Dzinnun, Yusriah; Nurmandi, Achmad; Purnomo, Eko Priyo (ijd-demos, 2020)
AbstractLevel of citizen participation has increased in the advent of digital government. A significant change in participation behavior through the Government's web 3.0 platform occurred in 2017, right after the Government of DKI Jakarta decided to move to the new web 4.0 platform without removing the previous one. Findings revealed that there is an overlapping and confusion in the community since both platforms are still running in the same time. However, there has been a significant drop in the level of e-participation on the web 3.0 platform, and yet based on the number of reports, there is no indication that the community has moved to the web 4.0 platform. This academic paper will analysis either the implementation of the new platform is a good idea or not by comparing the data gathered from the government Citizens Relationship Management (CRM) platform and the previous platform. Data gathered were analyzed by referring to sustainable and replicability aspect. Moreover, a policy analysis on prior and subsequently the changes are needed to examine either a new policy would lead to a better good governance practiceKeywords:Â  e-government, integrated governance, smart city, DKI jakartaÂ AbstrakTingkat partisipasi masyarakat meningkat dengan munculnya pemerintahan digital. Perubahan signifikan pada perilaku partisipasi melalui platform web 3.0 Pemerintah terjadi pada tahun 2017, tepat setelah Pemerintah DKI Jakarta memutuskan untuk pindah ke platform web 4.0 baru tanpa menghapus yang sebelumnya. Temuan mengungkapkan bahwa ada tumpang tindih dan kebingungan di komunitas karena kedua platform masih berjalan dalam waktu yang bersamaan. Namun, telah terjadi penurunan yang signifikan pada tingkat partisipasi elektronik pada platform web 3.0, namun berdasarkan jumlah laporan, tidak ada indikasi bahwa komunitas telah berpindah ke platform web 4.0. Makalah akademik ini akan menganalisis apakah implementasi platform baru itu ide yang baik atau tidak dengan membandingkan data yang dikumpulkan dari platform Citizens Relationship Management (CRM) pemerintah dan platform sebelumnya. Data yang terkumpul dianalisis dengan mengacu pada aspek keberlanjutan dan replikasi. Selain itu, analisis kebijakan tentang perubahan sebelumnya dan selanjutnya diperlukan untuk memeriksa apakah kebijakan baru akan mengarah pada praktik tata kelola yang lebih baik.Kata kunci: e-government, pemerintahan terintegrasi, smart city, DKI jakarta